STRATEGI KOMUNIKASI PEMASARAN TERPADU SENIMAN COFFEE STUDIO DALAM MEMPERKENALKAN KONSEP 4TH WAVE - Utami, Bella Putri; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Seniman Coffee Studio is a coffee shop located at Jalan Sriwedari no. 5 Ubud Gianyar and has evolved coffee from 1 st wave to the 4th wave that is currently happening in coffee-producing countries, one of which is Indonesia. The purpose of this study is to determine the integrated marketing strategy used by Seniman Coffee Studio to introduce the 4th wave concept. This study uses a descriptive qualitative approach with a post-positivism paradigm. This study used purposive sampling and snowball sampling techniques to determining the informants Data obtained by interview, non-participant observation, and documentation. The results of this study indicate the integrated marketing communication strategy (IMC) conducted by Seniman Coffee Studio in introducing the 4th wave concept by implementing a marketing mix with 4 elements, namely: product, place, price and promotion consisting of 8 elements (promotion mix) such as advertising, sales promotion, personal selling, direct marketing, public relations, and interactive marketing .   Keyword: Seniman Coffee Studio, 4 th Wave Concept, Integrated Marketing Communication Strategy,